Antioxidant Activity of Zodia (Evodia suaveolens) Protein Extract In Vitro - Fudhaili Ahmad; Purnama Erlix Rakhmad; Syamsudi Nur Anindya; Yolanda Rofiza (BIO Web of Conferences, 2024)
The zodia (Evodia suaveolens) plant is an Indonesian endemic that originated in Papua. Zodia leaves are empirically used as anti-mosquito and dysentery medications, and cooked bark is useful as a malaria fever reliever. Until present, no research has been conducted on the protein of the zodia plant extract that has demonstrated action. The goal of this study was to assess the antioxidant activity of the zodia plant protein extract as reflected by IC50 (inhibitory concentration). Various established procedures were used to determine antioxidant capacity, including radical cation, 2,2’-Azinobis 3-ethyl Benzothlazole-6-Sulfonic Acid (ABTS●+) assay, hydroxyl radical (OH●), and superoxide anion (O2●-) scavenging. Data analysis was determined using ANOVA and continued with Duncan. The soluble protein in the stem has much stronger free radical scavenging (ABTS●+, OH●, and O2●-) capabilities than the leaves and root. According to the research, soluble proteins in stems have a significant potential for usage as antioxidants.